Heparin-induced thrombocytopenia: A critical appraisal of clinical practice guidelines with the AGREE II instrument. Issue 166 (June 2018) - Wang, Ying; Ye, Zhi-Kang; Li, Ji-Feng; Cui, Xiang-Li; Liu, Li-Hong
Abstract: Background: Despite the availability of clinical practice guidelines (CPGs), the risk of death or thromboembolic complication associated with heparin-induced thrombocytopenia (HIT) remains high. Our aim was to systematically review the quality of CPGs for HIT and summarize the recommendations. Methods: CPGs for HIT were systematically searched on PubMed, Embase, guidelines' websites, and Google up to August 6, 2017. Independently, three appraisers assessed the quality of CPGs using the Appraisal of Guidelines for Research & Evaluation II (AGREE II) instrument and extracted the data. Recommendations were summarized, and a comparative study was conducted to analyze the consistency among guidelines. Results: A total of 11 CPGs were evaluated. The quality assessed by AGREE II varied widely, not only between domains within guidelines, but also between guidelines across domains. The domain of scope and purpose and clarity of presentation obtained the highest median scores, while the domain of rigor of development and editorial independence obtained the lowest median scores. The ACCP guideline and BSH guideline were recommended for use in dealing with HIT, achieving a score of at least 50% in all six AGREE II domains. Recommendations across guidelines were inconsistent, especially in the choice of non-heparin anticoagulant for HIT. Conclusions: Future HIT guidelines should place more emphasis on methodological quality and improve efforts to include cost and local availability of drugs when providing recommendations. Highlights: Quality of HIT guidelines was quite different. Domain of rigor of development and editorial independence were poorly described. Recommendations across guidelines were inconsistent. Future HIT guidelines should place more emphasis on methodological quality.